Impact of elevated CO2 on high temperature induced effects in grain yield of chickpea (Cicer arietinum) - PUJA RAI; ASHISH K CHATURVEDI; DIVYA SHAH; MADAN PAL (The Indian Journal of Agricultural Sciences, 2016)
High temperature and increasing atmospheric CO2 are debatable issues under climate variability and of major concern for agricultural productivity. Field experiments were conducted with two chickpea (Cicer arietinum L.) genotypes, viz. Pusa 1103 (desi) and Pusa 1105 (kabuli) to examine the role of elevated CO2 (570±86 µmol/mol) and high temperature (5.93±0.22ºC above ambient) on yield and biomass using Open top chambers and temperature tunnel respectively. Elevated CO2 enhanced the grain yield and biomass of both the chickpea genotypes by 34-47 and 39-55 percent respectively while, high temperature exposure reduced the yield of both the genotypes by 19-30 percent. Among genotypes, counter effect of CO2 to high temperature is more prominent in desi compared to kabuli which was attributed with more partitioning of assimilates toward pods in desi. While in kabuli genotypes the biomass partitioning was more towards vegetative plant parts attributing enhanced biomass. Study concludes that elevated CO2 could ameliorate the reductions in yield under high temperature by more dry matter partitioning towards pods instead of temperature induced partitioning towards vegetative plant parts.